Preparation and characterization of photocured thiol-ene hydrogel: Adsorption of Au(III) ions from aqueous solutions - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR (WILEY, 2012)
In this study, photocured a novel thiol-ene hydrogels based on P(Penta3MP4/PEG-DA/HEMA) were investigated for adsorption of Au(III) ions from aqueous solutions purposes. The photopolymerization kinetics of thiol-ene-based formulations was investigated by real-time infrared spectroscopy. The chemical composition and surface morphology of hydrogels were also characterized. The effect of different parameters on Au(III) adsorption efficiency was examined in detail. Better adsorption behavior was achieved for Au(III) by P(Penta3MP4/PEG-DA/HEMA) F1 hydrogels. The maximum uptake for Au(III) was at pH 0.5. Both Langmuir and Freundlich adsorption isotherm models were applied and the reusability of thiol-ene hydrogels investigated. (C) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: thiol-ene; hydrogel; pentaerythritol tetrakis (3-mercaptopropionate); Au(III) adsorption; METAL-IONS; SOLVENT-EXTRACTION; GOLD(III) IONS; GOLD; RECOVERY; SEPARATION; REMOVAL; EXCHANGE; RESINS; PRECONCENTRATION